Seasonal and spatial alterations in macrofaunal communities and in Nephtys cirrosa (Polychaeta) oxidative stress under a salinity gradient: a comparative field monitoring approach - Magalhães, Luísa (2020)
Sustainability of estuaries and lagoons is vital for coastal regions both in ecological and economic terms. These ecosystems are highly vulnerable to both natural and anthropogenic disturbances, with environmental risk assessment becoming increasingly challenging, and requiring the application of more adequate and accurate approaches that allow to distinguish between the eﬀects induced by anthropogenic factors from those related to organisms characteristics and/or ecosystem’s natural features. In this context and as a case study, the present study compared the responses to diﬀerent salinities analyzed through macrobenthic community composition (namely, species richness, abundance, alpha diversity, margalef richness and rarefaction index) inhabiting the Ria de Aveiro and on Nephtys cirrosa (polychaete species present in the studied community) oxidative stress markers (including, protein content, antioxidant enzymes activity and cellular damage). Overall, results conﬁrmed that macrofauna’s descriptors of community composition are highly suitable to assess the eﬀects of environmental salinity at both spatial and seasonal levels. Comparatively, biomarkers provided valuable informationonthe eﬀectsofenvironmentalchangesatthe sub-cellular levelinN.cirrosa,despiteshowedtobeless speciﬁctospatialandseasonalsalinityvariation,beinginﬂuenced byamultitudeofdiﬀerentabioticfactors.The present study emphasizes the importance of identifying the potential interfering factors and their impacts on the biomarker signals observed in wild populations and reinforce that in biomonitoring programs, biomarkers should be used as complementary tools.